Antibacterial Activity of Graptophyllum pictum (L.) Griff Extract using Variations of Ultrasonic Frequency against Escherichia coli - Oktavia, Sabina; Bahar , Meiskha; Wahyuningsih, Sri; Zulfa , Fajriati; Makkiyah, Feda Anisah (BIOEDUSCIENCE, 2024)
Background: Escherichia coli is a Gram-negative bacteria and is the main suspect for urinary tract infections and gastroenteritis. The cases of antibiotic resistance against E. coli continue to increase due to public non-compliance with taking antibiotics. Purple leaf (Graptophyllum pictum (L.) Griff) is a plant that grows widely in Indonesia and is generally used as a herbal medicine. This plant contains alkaloids, flavonoids, tannins, and steroids, which can inhibit bacterial growth. This content is obtained through an extraction process. This study aimed to determine the difference in effectiveness of purple leaves extracted using the Ultrasound-Assisted Extraction method at a frequency of 30 kHz, 40 kHz, and 50 kHz against the growth of E. coli. Methods: This research is purely experimental and was carried out in vitro. The antibacterial activity test used the suitable diffusion method, and then the diameter of the inhibition zone was measured. This research was analyzed using the Kruskal-Wallis and Mann-Whitney tests, which resulted in significant differences between treatment groups. Results: The average diameter of the inhibition zone produced at frequencies of 30 kHz, 40 kHz, and 50 kHz is 3,40 mm, 6,22mm, and 4,37mm. Conclusions: The results of this research show that the most optimal frequency is 40 kHz; this frequency can form cavitation in purple leaf cells, thereby producing phytochemical substances that can damage the cell structure of E. coli.